Reading Self-efficacy and Its Influence on Students' Reading Proficiency - Semi Sukarni (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The objective of the study is to analyze the influence of self-efficacy on students' reading proficiency. The research had been done in English Education Program of Purworejo Muhammadiyah University involving 62 students from two classes of the fifth semester. Self-efficacy questionnaire and reading comprehension test were used to collect the data. The data were analyzed by using descriptive and inferential analysis. To test the hypotheses correlation product moment and linear regression were applied. The finding shows that there is a positive and significant correlation between self-efficacy and reading proficiency as the r-value is 0.332 with sig. = 0.004 < 0.05. The regression test shows that self-efficacy contributes 11% to the achievement of reading proficiency while 89% was contributed by other factors. Self-efficacy has significant influence as the t-value 2.120 with significant level 0.000. The implication of the study is it is important to develop the students with positive self-efficacy during learning process as it can influence on their language achievement particularly in reading.